Let $X,Y$ be two independent negative binomial distributed random variables.

$X$ ~ $NB(r,p)$ and $Y$ ~ $NB(s,p)$

Show that:

$ X+Y $ ~ $ NB(r+s,p) $.

Remark: So where I'm stucked? I failed to show that $ \sum_{j=0}^{k} \binom{j+r-1}{j} \cdot \binom{k-j+s-1}{k-j} = \binom{k+r+s-1}{k}$. If I have this identity I can solve this exercise. First I thought that this is the vandermonde identity, but it isn't. So how can I show this identity? I know that I can solve this exercise by using the fact that a negative binomial distributed RV is a sum of geometric distributed RV, but i want to show it with my attempt.

Thank you for your help.


In general we have:$$\sum_{i+j=k}\binom{i}{r}\binom{j}{s}=\binom{k+1}{r+s+1}\tag1$$

This under the convention that $\binom{n}{k}=0$ if $k\notin\{0,1,\dots,n\}$.

For a combinatorial proof think of a row of $k+1$ balls.

Selecting $r+s+1$ of them can be done on $\binom{k+1}{r+s+1}$ ways (RHS).

Doing so we first pick out a ball that cuts the row in a left row of length $i\geq r$ balls and a right row of length $j\geq s$ balls. So this under the condition that $i+j=k$. Then from the left row we select $r$ balls and from the right row we select $s$ balls. This process reveals the LHS.

Your summation can be rewritten by:$$\sum_{i+j=k}\binom{j+r-1}{r-1}\binom{i+s-1}{s-1}=\sum_{i+j=k+r+s-2}\binom{j}{r-1}\binom{i}{s-1}$$

Then applying $(1)$ gives:$$=\binom{k+r+s-1}{r+s-1}=\binom{k+r+s-1}{k}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.